Legal Protection For Land Certificate Owner Which Coordinate Point Is Different With Land Object - Pusparukmi, Nirwanadewi; Witasari, Aryani (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2022)
Land as one of the agricultural sectors is an important factor for the people of Indonesia. Such is the importance of land for human life, so it is not surprising that every human being wants to own and control it. This desire to control often results in land problems and disputes in social life.The problems that will be examined in this research are: 1)How are the coordinates of the land object different from those listed on the certificate? 2) What is the legal protection for the certificate owner whose coordinates are different from those listed on the certificate? The method used in this research is empirical juridical, namely an approach based on applicable law and based on reality in practice. Based on the problems above, it is known that 1)The Head of the Land Office corrects the error by making a report on the correction, as stipulated in Article 41 paragraph (3) and (6) of the Agrarian Regulation/Head of BPN 3/1997, 2) Preventive legal protection, where legal subjects are given the opportunity to file objections or opinion, the aim is to prevent disputes from occurring.